2023
DOI: 10.1097/j.jcrs.0000000000001209
|View full text |Cite
|
Sign up to set email alerts
|

Two point four million cataract surgeries: 30 years with the Swedish National Cataract Register, 1992-2021

Abstract: The present review summarizes data collected by the Swedish National Cataract Register (NCR), which by the end of 2021 contained data for more than 2.4 million cataract surgeries between 1992 and 2021. During these 30 years, the cataract surgery rate rose from 3700 to 12 800. The coverage of NCR is very high including 93% of all cataract procedures in Sweden between 2010 and 2021. Independently of demographic changes, the proportion of operations of patients age 60 to 79 has increased while the proportion of 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 35 publications
0
2
0
Order By: Relevance
“…Our patients who displayed normal OCT RNFL results exhibited demographic characteristics and baseline IOP levels that closely matched those typically observed among cataract candidates (Table 1). 11–14 In addition, our patients with abnormal OCT RNFL scans were older compared with those with normal OCT RNFL scans, in line with the well-established trend of an increased incidence of glaucoma with advancing age (Table 1). 15 It is noteworthy that despite a 2 mm Hg higher mean IOP level in the group with abnormal OCT RNFL scans, both groups maintained IOP levels below the accepted threshold of 21 mm Hg for diagnosing of ocular hypertension or glaucoma, in line with recent reports on the under diagnosis of glaucoma.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…Our patients who displayed normal OCT RNFL results exhibited demographic characteristics and baseline IOP levels that closely matched those typically observed among cataract candidates (Table 1). 11–14 In addition, our patients with abnormal OCT RNFL scans were older compared with those with normal OCT RNFL scans, in line with the well-established trend of an increased incidence of glaucoma with advancing age (Table 1). 15 It is noteworthy that despite a 2 mm Hg higher mean IOP level in the group with abnormal OCT RNFL scans, both groups maintained IOP levels below the accepted threshold of 21 mm Hg for diagnosing of ocular hypertension or glaucoma, in line with recent reports on the under diagnosis of glaucoma.…”
Section: Discussionsupporting
confidence: 84%
“…23 The prevalence of glaucoma at the time of cataract surgery was reportedly 8% to 13% in large population studies. 12,14 Furthermore, glaucoma incidence and OCT RNFL abnormality in cataract candidates have been previously established; Pakuliene et al observed that patients with glaucoma undergoing cataract surgery had lower mean OCT RNFL thickness compared with healthy participants. 24 Abdelmassih et al reported that 14.2% of candidates for cataract surgery had abnormal OCT RNFL findings, and interestingly, 30% of those cases had no history of glaucoma and no detected anomaly on fundus examination.…”
Section: Discussionmentioning
confidence: 99%
“…NCR has been estimated to capture 93 % of all cataract surgeries in the country. The variables in the core register for all cataract procedures have been published, and their changes over the years since the foundation in 1992 are reported in the Swedish meta-database Register Utilization Tool through the Swedish Research Council [ 22 ]. For all matches in the NCR, we collected data on the date of cataract surgery, best corrected visual acuity (BCVA) pre- and post cataract surgery (of the tumor eye for UM patients, of the first eye undergoing cataract surgery for individuals from the general population), refractive surprise, details on the surgery including lens material and color, co-existing conditions at the time of cataract surgery such as glaucoma and pseudo exfoliations, and on the use of topical medications.…”
Section: Methodsmentioning
confidence: 99%
“…E.g., a UM patient will typically undergo regular follow-up visits with eye examinations, potentially increasing the likelihood that a cataract will be detected and that a referral for surgery will be sent compared to a person who does not undergo regular eye exams. Lastly, although our data encompasses all patients treated with plaque brachytherapy in Sweden, considering that we are the only institution in the country that offers this treatment, and the Swedish Cataract Register is estimated to have covered 93 % of cases from 2010 to 2021, we cannot discount the possibility that some cataract surgeries in the UM or general population sample were not accounted for [ 22 ].…”
Section: Limitationsmentioning
confidence: 99%